Genetic variation is predominantly structured by geography rather than host in feather mites (Acariformes: Sarcoptiformes) associated with tanagers (Aves: Thraupidae) in Brazil - Pedroso, Luiz Gustavo de A.; Klimov, Pavel B.; Hernandes, Fabio A. (Entomological Communications, 2021)
Feather mites are the most common ectosymbionts on birds. These obligatory symbionts are mainly transmitted during their host’s parental care, which creates high host specificity. Due to this intimate relationship, it is thought that their geographic distribution is restricted by their host distribution, or that a host species harbors the same mite composition across its whole range. However, our knowledge regarding the geographic distribution of feather mites remains scarce, with only a few studies indicating disconnections between mite and host distributions, especially in widespread hosts. Here, we investigate the feather mites distribution on four tanager species, three widespread – Thraupis sayaca (L.), T. palmarum (Wied), and Stilpnia cayana (L.) from Northern and Southern Brazil; and the Amazonian T. episcopus (L.). Feather mites were identified using the molecular barcode marker COX-1 using K2P genetic distances. We found a strong genetic structure between Northern and Southern populations of tanagers of more than 10%, even among conspecific hosts. Therefore, the mite distribution on Brazilian tanagers is predominantly shaped by geography rather than by host species. These features in turn reflect historical horizontal transmissions among the hosts, suggesting a high potential for frequent host switches in these symbionts.